Edition konsequent nr. 24c. Reprint aus: AIZ nr. 47, 1933. "Der Henker und die Gerechtigkeit" - Heartfield, John (1933)
Edition konsequent nr. 24c. Reprint aus: AIZ nr. 47, 1933. "Der Henker und die Gerechtigkeit".